Poverty and exclusion in the western balkans : new directions in measurement and policy - Savastano, Sara; Ruggeri Laderchi, Caterina (Economic Studies in Inequality, Social Exclusion and Well-Being, 2013)
This book maps the latest developments in the policy relevant analysis on poverty, inclusion and the social agenda in the Western Balkans. It does so by presenting a selection of recent papers which explore from a methodological and analytical point of view how the inclusion agenda can be monitored and adapted to understand the challenges in the region. The volume includes an overview and four sections, covering respectively: (1) innovations in terms of measurement of poverty and inclusion in the region (the concept of inclusion as elaborated at the EU level, innovations in survey design to suit the measurement of inclusion, methodological insights from qualitative work); (2) innovative country level analysis (updating poverty mapping in inter-censual years, the analysis of material deprivation, the analysis of determinants of social inclusion, subjective wellbeing of public work programs participants); (3) examples of country level analysis of drivers of exclusion (barriers to formalization in the labour market, gender disparities in the labour market, disruption in social networks following urbanizations, attitudes towards multi-ethnic states); (4) building inclusive safety nets (an assessment of safety nets in the region, the political economy of welfare reform, micro-simulations of social assistance reform, the adoption of better tools to improve targeting performance).   The chapters combine sophisticated techniques which are at the frontiers of poverty analysis (small area estimation, efficiency analysis applied to household welfare, micro-simulations) with less ground-breaking papers which take advantage of innovative datasets or perspectives deeply grounded in the policy dialogue in the countries of the region. By providing a wide spectrum of innovative and policy relevant analytical contributions this book will be of broader interest than for observers of the region.